2022
DOI: 10.1111/1744-7917.13004
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysis triggering hormone peptide in the African malaria mosquito Anopheles gambiae: The peptide structure for receptor activation

Abstract: Infections by mosquito‐borne diseases represent one of the leading causes of death in third world countries. The rapid progression of resistance to conventional insecticide causes a significant threat to the highly efficient preventive methods currently in place. Insect neuropeptidergic system offers potential targets to control the insect vectors. The essential roles of the neuropeptide ecdysis triggering hormone (ETH) in insect development and reproduction led us to attempt understanding of the fundamentals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…141 Furthermore, the well-identified insect neuropeptideergic system offers potential targets to control insect vectors. 142 It has been previously shown that residues 65−80 in HsSulf A, which includes the critical Cys at position 69, are essential for the interaction between HsSulf and HsSumf1 under in vitro microsome conditions. 143 Moreover, single or multiple amino acid mutational analyses on peptides-derived from HsSulfs demonstrated that a core motif, pentapeptide CXPSR (X stands for any amino acid), were crucial for the recognition of eukaryotic sulfatases by HsSumf1.…”
Section: Journal Of Agricultural and Food Chemistry Pubsacsorg/jafcmentioning
confidence: 99%
See 1 more Smart Citation
“…141 Furthermore, the well-identified insect neuropeptideergic system offers potential targets to control insect vectors. 142 It has been previously shown that residues 65−80 in HsSulf A, which includes the critical Cys at position 69, are essential for the interaction between HsSulf and HsSumf1 under in vitro microsome conditions. 143 Moreover, single or multiple amino acid mutational analyses on peptides-derived from HsSulfs demonstrated that a core motif, pentapeptide CXPSR (X stands for any amino acid), were crucial for the recognition of eukaryotic sulfatases by HsSumf1.…”
Section: Journal Of Agricultural and Food Chemistry Pubsacsorg/jafcmentioning
confidence: 99%
“…Subsequently, their roles expanded to encompass various development, morphogenesis, and reproduction aspects . Furthermore, the well-identified insect neuropeptide­ergic system offers potential targets to control insect vectors …”
Section: Application Prospects For P Xylostella By Targeting the Pxgs...mentioning
confidence: 99%
“…Ecdysis triggering hormone (ETH) was first discovered and located in the tracheal epithelial gland of Manduca sexta (Lepidoptera: Sphingidae) (Žitňan et al, 1996) and affects physiological functions upon binding to its receptors (Dembele et al, 2022; Park et al, 2003). Currently, ETH has been identified and is associated with moulting in insects, including Lepidoptera (Žitňan et al, 2002), Diptera (Park et al, 2002; Shi et al, 2017), Coleoptera (Arakane et al, 2008), Hemiptera (Roller et al, 2010), Hymenoptera (Roller et al, 2010), and Orthoptera (Lenaerts et al, 2017), as well as in Arachnida (Zhu et al, 2019) and crustaceans (Nhut et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, time-consuming methods for molecular prediction, such as nuclear magnetic resonance (NMR), can be replaced by such machine learning-based approaches. Nevertheless, for complex interactions in and between large macromolecules, such as the interaction between RNA and proteins and in-between proteins, experimental techniques, including but not limited to NMR and X-Ray crystallography, can be applied [28,29]. These laboratory techniques are also the basis for a commonly used approach for structural prediction based on homology modeling.…”
Section: Introductionmentioning
confidence: 99%